Ngumpul Dingsanak Sebuah Tradisi Pra Pernikahan Di Desa Keban Agung Kecamatan Lawang Kidul Kabupaten Muara Enim - Angela, Mahest Preety; Syawaluddin, Mohammad; Santosa, Santosa (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
This research is entitled The Value of Local Wisdom in the Pre-Wedding Dingsanak Gathering Tradition in Keban Agung Village, Lawang Kidul District, Muara Enim Regency. This research aims to find out how the process and implementation of the Dingsanak gathering alms tradition and its implementation in Keban Agung Village, Lawang Kidul District, Muara Enim Regency and the values contained in the dingsanak gathering tradition in Keban Agung village, Lawang Kidul subdistrict, Muara Enim district. The results of this research are the history of the dingsanak gathering tradition, local wisdom values in the dingsanak gathering tradition, namely: religious values, mutual cooperation values, harmony values, cultural values, and responsibility values, time and process of implementing the dingsanak gathering tradition, tools and materials to make a typical food gathering dingsanak, the Islamic values contained in the gathering dingsanak tradition are: Aqidah values, worship values and moral values.